2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793509
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Networks for Model-Based Control Under Partial Observation

Abstract: There has been an increasing interest in learning dynamics simulators for model-based control. Compared with off-the-shelf physics engines, a learnable simulator can quickly adapt to unseen objects, scenes, and tasks. However, existing models like interaction networks only work for fully observable systems; they also only consider pairwise interactions within a single time step, both restricting their use in practical systems. We introduce Propagation Networks (PropNet), a differentiable, learnable dynamics mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 16 publications
0
116
0
Order By: Relevance
“…With the objective to support the requirements of path planning and dynamic interaction of a robotic hand with a deformable object, Graph Neural Network (GNN) based models are also adapted in our framework to predict the future object state using the information of the current object state and the manipulation actions of the robotic hand. Specifically, we use the Interaction Network (IN) framework (Battaglia et al, 2016 ) along with its extension known as PropNet (Li et al, 2019b ) for supervised learning on graph structures. Unlike standard GNNs, the IN is specifically designed to learn the dynamics of physical interactive systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the objective to support the requirements of path planning and dynamic interaction of a robotic hand with a deformable object, Graph Neural Network (GNN) based models are also adapted in our framework to predict the future object state using the information of the current object state and the manipulation actions of the robotic hand. Specifically, we use the Interaction Network (IN) framework (Battaglia et al, 2016 ) along with its extension known as PropNet (Li et al, 2019b ) for supervised learning on graph structures. Unlike standard GNNs, the IN is specifically designed to learn the dynamics of physical interactive systems.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, several iterations of the algorithm are needed in order to propagate the information on the graph, and thus reach remote nodes. As an extension to IN, the PropNet (Li et al, 2019b ) formulation (Algorithm 4) proposes the inclusion of a multi-step propagation phase, which consists of computing the edge and node effects using an additional iterative process, where l corresponds to the current propagation step parameter, and is set to a value within the range of 1 ≤ l ≤ L . Also, the update functions, , , are used to encode the input edge and node features, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling dynamics directly in the pixel space is universal but challenging due to the intricate interplay between physics and graphics; an alternative is to separate perception from dynamics modeling, and learn dynamics from object states. Our recent work along this line has shown that a model that learns to approximate object dynamics can be useful for planning [Janner et al, 20191, generalize to scenarios where only partial observations are available [Li et al, 2019c], and discover physical object properties without supervision [Zheng et al, 2018]. We have further extended our model to particle-based representations, so that it can characterize the dynamics of soft robots [Hu et al, 2019] (Figure 1-3C) and of scenes with complex interactions among rigid bodies, deformable shapes, and fluids (Figure 1-3D).…”
Section: Dynamics: Learning With Physics Enginesmentioning
confidence: 99%
“…With the objective to support the requirements of path planning and dynamic interaction of a robotic hand with a deformable object, Graph Neural Network (GNN) based models are also adapted in our framework to predict the future object state using the information of the current object state and the manipulation actions of the robotic hand. Specifically, we use the Interaction Network (IN) framework (Battaglia et al, 2016) along with its extension known as PropNet (Li et al, 2019b) for supervised learning on graph structures. Unlike standard GNNs, the IN is specifically designed to learn the dynamics of physical interactive systems.…”
Section: Shape Predictionmentioning
confidence: 99%
“…Therefore, several iterations of the algorithm are needed in order to propagate the information on the graph, and thus reach remote nodes. As an extension to IN, the PropNet (Li et al, 2019b) formulation (Algorithm 4) proposes the inclusion of a multi-step propagation phase, which consists of computing the edge and node effects using an additional iterative process, where l corresponds to the current propagation step parameter, and is set to a value within the range of 1 ≤ l ≤ L. Also, the update functions, φ enc R , φ enc O , are used to encode the input edge and node features, respectively. While the function, φ dec O , is used to decode the output node feature.…”
Section: Propagation Networkmentioning
confidence: 99%